1997
DOI: 10.1074/jbc.272.45.28191
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Intermediates Are Involved in the Induction of CD95 Ligand mRNA Expression by Cytostatic Drugs in Hepatoma Cells

Abstract: Oxidative stress has been associated with the induction of programmed cell death. The CD95 ligand/receptor system is a specific mediator of apoptosis. We have used the model of drug-induced apoptosis to assess whether the CD95 ligand mRNA is induced by reactive oxygen intermediates. Treatment of HepG2 hepatoma cells with bleomycin induced the production of reactive oxygen intermediates and, as an additional parameter of oxidative stress, resulted in glutathione (GSH) depletion. In parallel, CD95 ligand mRNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(87 citation statements)
references
References 29 publications
(29 reference statements)
5
77
1
3
Order By: Relevance
“…This is daring to speculate because both normal and AT transformed lymphoblasts show high constitutive NF-kB activity (data not shown), probably consecutive to maturation in B cells before EBV transformation, but AT lymphoblasts remain hypersensitive to ionizing radiation (Lavin and Shiloh, 1997). In addition, some reports indicate that NF-kB does not a ect or even promote programmed cell death in some systems (Kasibhatla et al, 1998;Hug et al, 1997). Jung et al (1998) recently showed that the N-terminally truncated IkBa protein that complements the AT phenotype in AT5BIVA cells (Jung et al, 1995) diminishes apoptosis in AT cells but enhances apoptosis in normal (MRC5-CV1) Âźbroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…This is daring to speculate because both normal and AT transformed lymphoblasts show high constitutive NF-kB activity (data not shown), probably consecutive to maturation in B cells before EBV transformation, but AT lymphoblasts remain hypersensitive to ionizing radiation (Lavin and Shiloh, 1997). In addition, some reports indicate that NF-kB does not a ect or even promote programmed cell death in some systems (Kasibhatla et al, 1998;Hug et al, 1997). Jung et al (1998) recently showed that the N-terminally truncated IkBa protein that complements the AT phenotype in AT5BIVA cells (Jung et al, 1995) diminishes apoptosis in AT cells but enhances apoptosis in normal (MRC5-CV1) Âźbroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with data recently published showing that bleomycininduced CD95-L mRNA involves ROS in hepatoma cells. 48 Furthermore, downregulation of CD95 expression was not found in chemosensitive cells after pretreatment with NAC or GSH at time points used in these experiments (data not shown). Defective activation of caspases by cytotoxic drugs after pretreatment with NAC or GSH was also reflected by the failure to cleave the prototype caspase substrate poly(ADP-ribose)polymerase (PARP).…”
Section: Effects Of Nac and Gsh On Doxorubicin-induced DC M Reductionmentioning
confidence: 90%
“…25 Furthermore, it was found, that CD95-L mRNA induction involves ROS in hepatoma cells treated with bleomycin. 48 GSH has also been found to modulate T-cell apoptosis e.g. during HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms on how two distinct apoptotic cascades are simultaneously activated by cytotoxic drugs are not understood. For the Fas-mediated apoptotic pathway, cytotoxic drugs are reported to promote FasL expression and FasL-Fas interaction (Hug et al, 1997, Kasibhatla et al, 1998. In the present study, we used g-irradiation and cisplatin to trigger DNA damage.…”
Section: Discussionmentioning
confidence: 99%